Comparative analysis of single-axis solar tracker performance with and without reflector under various weather conditions - Kusuma, Vicky Andria; Firdaus, Aji Akbar; Suprapto, Sena Sukmananda; Yuniar, Risty Jayanti; Trimulya, Hanif; Priyanto, Yun Tonce Kusuma (International Journal of Applied Power Engineering (IJAPE), 2024)
This research explores a sun tracking system for solar panels that affects the power output of the panels. To address this, a unidirectional sun tracking system is implemented to ensure the solar panels are perpendicular to the sun, thus optimizing solar radiation. Additionally, reflectors are integrated to capture more sunlight. This research aims to design the system of unidirectional sun tracking to enhance the power output generated by solar panels and compare its performance with stationary (static) solar panels. The results demonstrate that the system of sun tracking improves the power output of solar panels. However, when reflectors are used in conjunction with the sun tracking system, no significant increase in power output is observed. Moreover, solar panels equipped with the unidirectional sun tracking system exhibit a power increase of 52.06 Watts compared to stationary solar panels. This research indicates that employing a unidirectional sun tracking system with the addition of reflectors does not enhance power output but instead reduces it due to the increased temperature effect caused by the sunlight reflection from the added reflectors.